PENGARUH JUMLAH PENDUDUK MISKIN DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Lidyawati Padang; Murtala Murtala (JURNAL EKONOMIKA INDONESIA, 2020)
This study aims to determine the effect of the number of poor people and the open unemployment rate on economic growth in Indonesia. This study uses panel data from 2015 to 2019. The method of data analysis used is panel data regression analysis. The results of the study partially show that the number of poor people has a negative and significant effect on economic growth in Indonesia, and the open unemployment rate has a negative and significant effect on economic growth in Indonesia. Simultaneously, the number of poor people and the open unemployment rate have a positive and significant effect on economic growth in Indonesia.